Respuesta :

For starters, find the common change in the terms, in this case each goes down by 3. This lets you know you're gonna have a -3n in your equation as each term decreases by 3. Your equation should be in f(n)=c+rn form, with r being change in f(n), or -3 in this case. This gives you f(n)=c-3n. Now, solve for c, add 3n to both sides to get f(n)+3n=c. Plug in your n of 1 and f(n) of 20 to get c=20+3(1)=23. Plug in your c to your f(n) formula to get f(n)=23-3n as your f(n) function.

f(n) the term in the sequence is f(n)=23-3n.

The given arithmetic sequence is 20, 17, 14, 11, 8, . . .

What is nth term of arithmetic sequence?

The nth term of the arithmetic sequence is [tex]a_{n}=a+(n-1)d[/tex].

From the given sequence, a=20 and d=17-20=-3.

Now, f(n)=20+(n-1)(-3)

⇒f(n)=20-3n+3

⇒f(n)=23-3n

Therefore, f(n) the term in the sequence is f(n)=23-3n.

To learn more about the arithmetic sequence visit:

https://brainly.com/question/12952623.

#SPJ6